Learning style preferences of college students using big data (2019)
Learning styles is one of the most studied topics in the field of education and the research results have generated relevant changes in the teaching-learning process. Currently, there are several theoretical models that explain the characterization and development of learning styles from different points of view, some of them share concepts, while others completely differ. The research focuses on the learning styles of higher education students for improving the quality of the educational process at the university. The results allow the recognize the learning style preferences of college students from different careers, and enable teachers to properly guide the learning activities by selecting the best teaching strategies, thus contributing to raise the quality of education. The results are expected to be relevant for further researches.